Optimization of the Convention on Elimination of All Forms of Discrimination Against Women in Divorce Cases in Indonesia - Al Ayubi, Solakhudin; Zumrotun, Siti (STIT Sunan Giri Bima, 2025)
After the ratification of the Convention on Elimination of All Forms of Discrimination Against Women (CEDAW), the issue of women's equality and anti-discrimination against Indonesian women has not been optimal. Indonesia tries to achieve women's equality and eliminate discrimination against women in marriage regulations. However, many things can still be criticized by thinkers regarding the harmony between the law and the reality that is developing in society. The researchers use a qualitative method in this article, with data collection based on phenomenological principles based on the ruling of the Religious Court. This article attempts to provide a complete overview of an important issue that has yet to be addressed in the law itself after the ratification of CEDAW with Law Number 7 of 1984 and to see how far the optimization of the design of laws and regulations and the development of indicators/parameters based on CEDAW. Through this article, readers can be aware of the achievement of optimizing the implementation of the Convention on Eliminating all forms of Discrimination against women due to divorce lawsuits. Asserting women's rights and addressing post-divorce discrimination remain important issues, particularly regarding economic rights, which are often unequal.